2003
DOI: 10.1046/j.1365-2648.2003.02748.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual determinants of research utilization: a systematic review

Abstract: Important conceptual and measurement issues with regard to research utilization could be better addressed if research in the area were undertaken longitudinally by multi-disciplinary teams of researchers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
356
1
15

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(395 citation statements)
references
References 33 publications
18
356
1
15
Order By: Relevance
“…The data illustrate the role that an affiliation to more abstract forms of knowledge may play in this regard (21,15). In line with the findings of Estabrooks et al (8) and Egerod & Hansen (13), our informants seem to have a positive attitude towards research utilization. The reason for knowledge-utilization seems to encompass both instrumental and conceptual purposes (18).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The data illustrate the role that an affiliation to more abstract forms of knowledge may play in this regard (21,15). In line with the findings of Estabrooks et al (8) and Egerod & Hansen (13), our informants seem to have a positive attitude towards research utilization. The reason for knowledge-utilization seems to encompass both instrumental and conceptual purposes (18).…”
Section: Resultssupporting
confidence: 90%
“…The author would like to express her gratitude to the ProLearn group: www.pfi.uio.no/prolearn/ Accepted for publication 8 …”
Section: Acknowledgementmentioning
confidence: 99%
“…An effective approach to knowledge mobilization must not only seek to reimagine how research content is produced and distributed, but must also address the barriers that users face in accessing and utilizing research knowledge, including lack of time, resources, skills, organizational support, and the perception that research is not valuable, timely, or relevant (Estabrooks, Floyd, Scott-Findlay, O'Leary, & Gushta, 2003;Walter et al, 2003). is is where design thinking may have something to contribute to our understanding of effective knowledge mobilization practices.…”
Section: The Researcher As Designermentioning
confidence: 99%
“…Lack of research utilisation is well described in different disciplines and several studies highlight barriers to, and facilitators for, research utilisation in nursing care [7][8][9][10] . Studies have shown that it was a complexity of multiple factors that was affecting nurses' research utilisation.…”
mentioning
confidence: 99%
“…In one review [10] six contextual factors relating to research utilisation were identified, the role of the nurse, access to resources, organisational climate, support, time for research activities, and provision of education. In another review, Estabrooks and colleagues [7] identified six individual determinants for research utilisation; beliefs and attitudes, involvement in research activities, information seeking, professional characteristics, education, and other socioeconomic factors. Kocaman and colleagues [8] described that the most commonly perceived barrier to research utilisation by nurses was lack of time.…”
mentioning
confidence: 99%